2014
DOI: 10.3109/21681805.2014.909530
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine cystitis: practical considerations in management

Abstract: Ketamine cystitis is a complex problem whose exact pathological mechanism and natural history remain unknown. The only known effective treatment is to abstain from the drug. Urologists need to recognize the condition early and work together with the local substance misuse service, focusing on drug cessation therapy to reduce complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 14 publications
0
29
1
Order By: Relevance
“…While ketamine-induced urinary symptoms and pathology have sometimes been referred to as ketamine cystitis in the literature [12], the urological sequelae of ketamine abuse extend beyond the lower urinary tract. In the 59 patients with ketamine abuse reported by Chu et al [9], 30 (51%) were found to have either unilateral or bilateral hydronephrosis in the initial assessment.…”
Section: Discussionmentioning
confidence: 99%
“…While ketamine-induced urinary symptoms and pathology have sometimes been referred to as ketamine cystitis in the literature [12], the urological sequelae of ketamine abuse extend beyond the lower urinary tract. In the 59 patients with ketamine abuse reported by Chu et al [9], 30 (51%) were found to have either unilateral or bilateral hydronephrosis in the initial assessment.…”
Section: Discussionmentioning
confidence: 99%
“…However, none have shown lasting or significant success, especially if ketamine abuse continues 2. Treatment failure and disease progression often requires more invasive management ranging from hydrodistension to urinary diversion and augmentation cystoclasty 4 5. In contrast, few studies have commented on upper tract involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Urologists focus on lower urinary symptoms because of several uncomfortable to the abusers, potential upper urinary lesions may be neglected by doctors. Recently, some serious upper urinary cases had been reported, and a separate attention should be paid on upper urinary tract including ketamine‐induced cystitis . We would like to update recent evidences on ketamine‐induced upper urinary tract lesions, and emphasis more attention on upper urinary tract system.…”
Section: Dear Editormentioning
confidence: 99%
“…According to clinical prospective researches and retrospective cases summaries, the incidence of hydronephrosis (bilateral or unilateral) ranged from 6% to 64.3% in different centers . Upper urinary tract lesions may be caused by these reasons: (i) contracted, overactive bladder, and decreased compliant bladder; (ii) vesicoureteric reflux; (iii) ureteric wall thickness or obstruction; (iv) abnormal ureter peristalsis; and (v) acute papillary necrosis. The actual mechanisms of katemine‐induced upper urinary tract lesions need advanced investigations.…”
Section: Dear Editormentioning
confidence: 99%